Jezikovna politika Republike Slovenije in potrebe uporabnikov - Gliha Komac, Nataša (Slavia Centralis, 2020)
Language Policy of the Republic of Slovenia and the Needs of Us The paper provides an overview of methodological premises of the target research project Language Policy of the Republic of Slovenia and the Needs of Users, whose central objective was to inventory the actual needs of language users in the Republic of Slovenia and Slovenian language users in neighbouring countries and elsewhere in the world. This is a unique and comprehensive attempt at active integration of language users in the making of future language policy to the widest possible extent. The project was carried out by researchers and experts with good knowledge of different areas of public life in the Republic of Slovenia and the life of Slovenian language community outside the Republic of Slovenia, legal experts having played a very important role. Different groups of language users, i.e. both specialized and general language users, were invited to participate in the online survey.